Answer:
The simplified form of -6.3x+14 and 1.5x-6 is -4.8x+8
Step-by-step explanation:
We have to simplify the following
-6.3x+14 and 1.5x-6
it can be written as:
=(-6.3x+14) + (1.5x-6)
Adding the like terms
=(-6.3x+1.5x)+(14-6)
= (-4.8x)+(8)
= -4.8x+8
So, the simplified form of -6.3x+14 and 1.5x-6 is -4.8x+8
Answer:
2÷45 - 76<em><u> </u></em><em><u>and </u></em><em><u>the </u></em><em><u>answer </u></em><em><u>is </u></em><em><u>yours</u></em>
Answer:
Step-by-step explanation: I would say y=x+2 or 2 because every number that you add 2 to, it gives you the solution which is the second number
Hope this helps!!!!
Please mark Brainliest!!!!!☺
Answer:
298
Step-by-step explanation: